A new type of hemophore-dependent heme acquisition system of Serratia marcescens reconstituted in Escherichia coli. - Ghigo, J M (1997)
The utilization by Serratia marcescens of heme bound to hemoglobin requires HasA, an extracellular heme-binding protein. This unique heme acquisition system was studied in an Escherichia coli hemA mutant that was a heme auxotroph. We identified a 92-kDa iron-regulated S. marcescens outer membrane protein, HasR, which alone enabled the E. coli hemA mutant to grow on heme or hemoglobin as a porphyrin source. The concomitant secretion of HasA by the HasR-producing hemA mutant greatly facilitates the acquisition of heme from hemoglobin. This is the first report of a synergy between an outer membrane protein and an extracellular heme-binding protein, HasA, acting as a heme carrier, which we termed a hemophore.